HIV, other sexually transmitted infections, and risk behaviors among female sex workers in Liuzhou, China. Issue 1 (January 2015) - Fan, Yin-Guang; Liu, Jin-Ji; Zhang, Yu-Jing; Dai, Se-Ying; Li, Ming-Qiang; Ye, Dong-Qing
Abstract: Objective: To determine the prevalence of infections with HIV and hepatitis C virus (HCV), and of syphilis among female sex workers (FSWs) in Liuzhou, China, along with levels of HIV-related knowledge and frequencies of risk behaviors. Methods: A cross-sectional survey was conducted between July 2012 and January 2013. FSWs (aged ≥ 16 years; reported receiving payment for sex in previous 6 months) working at 58 selected commercial sex establishments (level 1 [>¥300 per transaction], level 2 [¥100–300], or level 3 [<¥100]) completed a questionnaire and provided blood samples for testing. Results: Of 622 participating FSWs, 7 (1.1%) had HIV infection, 67 (10.8%) syphilis, and 44 (7.1%) HCV infection. Consistent condom use during commercial sex encounters in the past month was reported by 412 (66.2%) FSWs. Inconsistent condom use was most likely in FSWs working in level 3 establishments (odds ratio [OR] 1.85; 95% CI 1.02–3.39), with a regular partner (OR 1.65; 95% CI 1.12–2.45), and who used illicit drugs (OR 2.10; 95% CI 1.24–3.54). Inconsistent condom use was least likely in FSWs with high HIV awareness (OR 0.29; 95% CI 0.18–0.48) and who had had a previous HIV test (OR 0.51; 95% CI 0.34–0.76). Conclusion: Further prioritized and combined programs aimed at FSWs are needed to prevent HIV transmission in China.